The Discourse of Humanity in COVID-19 Pandemic - Fadhilah Permata Nira; Maula Hudaya; Rizky Anggia Putri (Advanced Studies on Socio-Economy Development, 2022)
Indonesia is one of the countries that are willing to accept the arrival of refugees to its territory. Although it has not yet ratified the 1951 Refugee Convention and the 1967 Protocol of the United Nations High Commissioner for Refugees (UNHCR), Indonesia has issued Peraturan Presiden Nomor 125/2016 on international refugees. In addition, the Indonesian government, especially President Joko Widodo, issued various statements which mostly emphasized fulfilling rights and upholding humanity for refugees demonstrating Indonesia's commitment to carrying out the human values contained in the Preamble of Undang-Undang Dasar 1945 and Pancasila as a dominant discourse of Indonesia's strategic culture. However, the discourse seems to have shifted in the era after the COVID-19 pandemic which has also potentially changed the Indonesian government's treatment of refugees. The negative impacts in various sectors made Indonesia have to prioritize the safety of its citizens and potentially neglect the fulfillment of the rights of refugees. Indonesia's burden in handling refugees during the pandemic is exacerbated by the unresponsiveness of UNHCR and the International Organization for Migration (IOM) which should be responsible for handling refugees. This leaves groups of refugees in a vulnerable condition because they are neglected by the Indonesian government both at the central and regional levels. Therefore, this paper tries to analyze aspects behind the shift in the Indonesian government's policy regarding foreign refugees using strategic cultural discourse and provide advice to the Indonesian government for handling refugees in pandemic and/or after pandemic situations without forgetting the humanitarian aspect of refugees. Keywords: Humanity, Strategic Culture, COVID-19, Refugees, Indonesian Government